Paternal mosaicism in ASXL3-related bainbridge-ropers syndrome: implications for genetic counseling and prenatal diagnosis - Zhao, Bowen; Ding, Fengjuan; Hou, Fei; Jin, Hua (Frontiers in Pediatrics, 2025)
ObjectiveBainbridge-Ropers syndrome (BRS) is a neurodevelopmental disorder predominantly caused by pathogenic variants in the ASXL3 gene, which have been conventionally considered to occur de novo. This study aimed to investigate the potential role of parental mosaicism in BRS inheritance and its clinical implications for genetic counseling.MethodsTrio-based whole-exome sequencing (WES) was performed on the proband and both parents to identify candidate variants, which were subsequently validated by Sanger sequencing. ASXL3-targeted ultra-deep sequencing of paternal semen DNA was then carried out to detect low-level mosaicism. Prenatal diagnosis via amniocentesis was used to evaluate transmission of the familial variant.ResultsWe definitively diagnosed this family by WES and found the lowest level of paternal mosaicism reported to date, with a peripheral blood variant allele frequency (VAF) of 8.17% and a semen VAF of 15.03%. Prenatal diagnosis at 18 weeks of gestation confirmed that the variant was not detected in this pregnancy.ConclusionThis study establishes parental chimerism as an important genetic mechanism for ASXL3-associated disorders and emphasizes the need for ultrasensitive testing in genetic counseling. The findings redefine genetic risk stratification for BRS and provide a basis for accurate family planning based on high-depth sequencing.